1999
DOI: 10.1152/ajpcell.1999.276.1.c46
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of the skeletal muscle Ca2+ release channel alters calmodulin binding

Abstract: This study presents evidence for a close relationship between the oxidation state of the skeletal muscle Ca2+ release channel (RyR1) and its ability to bind calmodulin (CaM). CaM enhances the activity of RyR1 in low Ca2+ and inhibits its activity in high Ca2+. Oxidation, which activates the channel, blocks the binding of125I-labeled CaM at both micromolar and nanomolar Ca2+concentrations. Conversely, bound CaM slows oxidation-induced cross-linking between subunits of the RyR1 tetramer. Alkylation of hyperreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 39 publications
4
55
0
Order By: Relevance
“…The molecular mechanism of activation and inhibition of RYR1 by CaM is unknown. We have previously shown with RYR1 (10,11,18,19) CaM and apoCaM using different determinants within the same region. We have also previously shown that this region is at a subunit-subunit interface within the RYR1 tetramer (20), suggesting the possibility that CaM may regulate RYR1 function by regulating the interactions between subunits.…”
Section: Discussionmentioning
confidence: 94%
“…The molecular mechanism of activation and inhibition of RYR1 by CaM is unknown. We have previously shown with RYR1 (10,11,18,19) CaM and apoCaM using different determinants within the same region. We have also previously shown that this region is at a subunit-subunit interface within the RYR1 tetramer (20), suggesting the possibility that CaM may regulate RYR1 function by regulating the interactions between subunits.…”
Section: Discussionmentioning
confidence: 94%
“…Intersubunit Cross-linking from NEM Alkylation-The activity of RYR1 is modulated by modification of its cysteine residues by oxidation (8 -10), alkylation (11,12,19) or nitrosylation (6,7,11,20). The cysteine residues involved in these reactions have not previously been identified.…”
Section: Cam Protects Both Cysteines Required For Oxidation-inducedmentioning
confidence: 99%
“…Other sulfhydryls also react rapidly with this reagent, in particular, the cysteines that alter the ability of RYR1 to bind CaM. Alkylation of less than 5% of the total RYR1 sulfhydryls completely blocks 35 S-apoCaM binding to RYR1, without altering the ability of RYR1 to bind either 35 S-Ca 2ϩ -CaM or [ 3 H]ryanodine (12). However, both Ca 2ϩ -CaM and apoCaM can protect this site from NEM inactivation (data not shown), suggesting a steric inhibition of 35 S-apoCaM, but not 35 S-Ca 2ϩ -CaM binding.…”
Section: Cam Protects Both Cysteines Required For Oxidation-inducedmentioning
confidence: 99%
See 2 more Smart Citations